Exploratory study for a habitational densification process, without parking, in the Hypercentre of Quito - Hurtado Vásquez, Diego (2018)
In this study, carried out in the city of Quito, in an area with a small fixed population, in which the majority of citizen activities are concentrated, it is verified that if the minimum parking requirement required by the current ordinance is eliminated, will be able to obtain lower-cost housing, affordable for larger population strata, in order to contribute to densify it and reduce urban sprawl. The concept of Transport Oriented Development (ITDP, 2014) is applied in the research, which proposes that densities should be densified in places where there are good public transport systems, equipment, shops and services, in order to reduce dependence on the automobile private, which in turn allows reducing vehicular traffic lanes and parking spaces, recovering the public space for pedestrians, cyclists and for the development of multiple citizen activities.